Association of thyroid transcription factor‐1 with the efficacy of immune‐checkpoint inhibitors in patients with advanced lung adenocarcinoma. Issue 16 (8th July 2022) - Nakahama, Kenji; Kaneda, Hiroyasu; Osawa, Masahiko; Izumi, Motohiro; Yoshimoto, Naoki; Sugimoto, Akira; Nagamine, Hiroaki; Ogawa, Koichi; Matsumoto, Yoshiya; Sawa, Kenji; Tani, Yoko; Mitsuoka, Shigeki; et al.
Abstract: Background: We aimed to identify the relationship between thyroid transcription factor‐1 (TTF‐1) expression of lung adenocarcinoma and the efficacy of immune‐checkpoint inhibitor (ICI) therapy. Methods: This retrospective multicenter study comprised patients with advanced lung adenocarcinoma treated with ICI monotherapy. We collected clinical medical records including data on TTF‐1 expression and analyzed the relationship between TTF‐1 expression and programmed death‐ligand 1 tumor proportion score (PD‐L1 TPS), objective response rate (ORR), progression‐free survival (PFS), and overall survival (OS). Results: In total, 108 patients with lung adenocarcinoma were analyzed. The rate of TPS ≥1% and ≥50% in patients with positive TTF‐1 expression was significantly higher than that in patients with negative TTF‐1 expression (88% vs. 60%, p < 0.001; 65% vs. 24%, p < 0.001). The ORR was significantly higher in TTF‐1 positive patients than in TTF‐1‐negative patients (38% vs. 8%, p = 0.003). Among patients with TPS ≥50% and 1%–49%, the ORR in TTF‐1 positive and negative patients was 48% (26/54) versus 17% (1/6) ( p = 0.21), and 32% (6/19) versus 11% (1/9) ( p = 0.37), respectively. The ORR for patients with TPS <1% was 0% in both the TTF‐1 negative and positive cases. The median PFS and OS was significantly longer in TTF‐1‐positive patients than in TTF‐1‐negative patients (5.4 vs. 1.6 months, p < 0.001; 18.2 vs. 8.0 months, p = 0.041). Multivariate analysis revealed that TTF‐1‐negative status was an independent unfavorable prognostic factor for PFS. Conclusion: Patients with TTF‐1‐positive status receiving ICI monotherapy showed better outcomes than those with TTF‐1‐negative lung adenocarcinoma. Abstract : This multicenter retrospective study investigated the association between immune‐checkpoint inhibitor monotherapy effectiveness and the expression status of thyroid transcription factor 1 (TTF‐1) in 108 patients with advanced lung adenocarcinoma and showed that programmed death‐ligand 1 tumor proportion score, objective response rate, progression‐free survival, and overall survival were significantly lower in patients with TTF‐1‐negative expression than those in TTF‐1‐positive patients.